Teachers’ Role In Fostering Efl Learners’ Positive Beliefs About Language Learning: The Case Of Teachers At M’sila University - refice, noureddine; yahiaoui, habib (El Omda in Linguistics and Discourse Analysis, 2025)
This study investigates the strategies EFL teachers use to foster positive beliefs about English language learning. Using a 19-item survey with 23 teachers, analyzed through statistical and qualitative methods, the findings reveal that teachers consider learners’ beliefs essential to language learning success. Many teachers support the inclusion of belief-awareness activities in lessons, viewing these as tools for enhancing students’ self-awareness and motivation. Teachers perceive students’ awareness of their own beliefs as moderate, indicating this as an area for further development. They actively work to create supportive learning environments by employing motivational, reflective, and real-world strategies. Despite challenges like student anxiety, fixed mindsets, and limited English exposure outside of school, teachers express confidence in their ability to positively shape students’ beliefs. Overall, the study highlights the critical role teachers play in cultivating positive beliefs, suggesting that engaging students in belief-awareness activities can significantly boost motivation and improve learning outcomes in EFL classrooms.